Social Sustainability, Past and Future Undoing Unintended Consequences for the Earth's Survival - van der Leeuw, Sander (Humanities, 2019)
For a professional, educated non-academic audience, this book asks how our societies were caught in a socio-economic dynamic causing the sustainability conundrum. It develops an original view of social evolution as the history of human information-processing, studying the past to understand the present in order to deal with the future. This title is also available as Open Access.